Effectiveness of Insulin Therapy Optimization in Type 2 Diabetes Mellitus Patients: A Prospective Observational Study - Murthy, Sudha; Yadav, Shekhar; George, Blessy; Ramaiah, Balakeshwa (Indian Journal of Pharmacy Practice)
Background: Type 2 Diabetes Mellitus, is an emerging complex metabolic disorder characterized by insulin resistance, impaired glucose uptake and disrupted hepatic glucose production. This study aimed to elucidate the importance of insulin therapy in optimizing glycemic control among T2DM patients. Materials and Methods: This prospective, observational study was performed in a tertiary care hospital, Bengaluru. The patient who was prescribed insulin and those already on insulin therapy were interviewed, based on their socio-demographics, insulin therapy, knowledge, and reason to initiate insulin therapy and data was documented in a standard data collection form. Results: The analysis population comprised 106 patients. The findings revealed a preponderance of patients (50-59 years) afflicted with T2DM, with a significant proportion (83.96%) initiating insulin therapy. Less than 40% of patient had a poor understanding of the disorder which co-relates to their non-adherence. 95% of the study population accounts for higher HbA1c, increased fasting sugars and uncontrolled diabetes on OHA’s were the major criteria to initiate insulin. Notably, hyperglycemia (89.62%) and diabetic neuropathy (84.90%) emerged as prevalent comorbidities. Difficulty in remembering and pain were reasons for refusal. Patients received comprehensive counselling, to enhance their adaptability and proficiency in managing insulin therapy. Conclusion: This study concludes that timely initiation of insulin therapy can minimize complications and patients’ adherence towards insulin, understanding, and physical activity will improve the efficacy and outcome of therapy. Proper counselling would help improve the patient’s specific problems.
Keywords: Insulin regimen; Types of insulin; Diabetes mellitus; HbA1c; OHA